The Droplet Digital PCR: A New Valid Molecular Approach for the Assessment of B-RAF V600E Mutation in Hairy Cell Leukemia - Guerrini, Francesca; Paolicchi, Matteo; Ghio, Francesco; Ciabatti, Elena; Grassi, Susanna; Salehzadeh, Serena; Ercolano, Giacomo; Metelli, Maria R.; Del Re, Marzia; Iovino, Lorenzo; Petrini, Iacopo; Carulli, Giovanni; et al. (Frontiers in Pharmacology, 2016)
Hairy cell leukemia (HCL) is a chronic lymphoproliferative B-cell disorder where the B-RAF V600E mutation has been recently detected, as reported for solid neoplasias but not for other B-cell lymphomas. The digital droplet PCR (dd-PCR) is a molecular technique that, without standard references, is able to accurately quantitate DNA mutations. ddPCR could be an useful instrument for the detection of the B-RAFV600E mutation in HCL, where the minimal residual disease monitoring is fundamental for planning a patients-targeted treatment in the era of new anti-CD20 and anti-RAF compounds. This retrospective study enrolled 47 patients observed at the Hematology Unit of the University of Pisa, Italy, from January 2005 to January 2014: 27 patients were affected by “classic” HCL, two by the variant HCL (vHCL), and 18 by splenic marginal zone lymphoma (SMZL). The aim of the study was to compare dd-PCR to “classic” quantitative PCR (QT-PCR) in terms of sensitivity and specificity and to demonstrate its possible use in HCL. Results showed that: 1) the sensitivity of dd-PCR is about half a logarithm superior to QT-PCR (5x10-5 versus 2.5x10-4); 2) the specificity of the dd-PCR is comparable to QT-PCR (no patient with marginal splenic lymphoma or HCL variant resulted mutated); 3) its high sensitivity would allow to use dd-PCR in the monitoring of MRD. At the end of treatment, among patients in complete remission, 33% were still MRD-positive by dd-PCR versus 28% by QT-PCR versus 11% by the evaluation of the B-cell clonality; after 12 months, dd-PCR was comparable to QT-PCR and both detected the B-RAF mutation in 15% of cases defined as MRD-negative by IgH rearrangement. Moreover, 4) the feasibility and the costs of dd-PCR are comparable to those of QT-PCR. In conclusion, our study supports the introduction of dd-PCR in the scenario of HCL, also during the follow-up.